1999
DOI: 10.1111/j.1471-0528.1999.tb08188.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of labour and maternal oxytocin infusion on fetal plasma oxytocin concentration

Abstract: It is not known whether human labour is associated with increased fetal oxytocin production or transfer of oxytocin across the placenta. Previous reports are contradictory, due in part, to the influence of maternal analgesia on fetal production. We determined plasma oxytocin concentration in the umbilical artery and vein of women after vaginal delivery and after caesarean section with general anaesthesia before or after the onset of labour. The results demonstrate that fetal production of oxytocin is not influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 18 publications
2
28
0
Order By: Relevance
“…This efficacy may be supported by our results since the uterus was able to respond to oxytocin at advanced stages of the parturition process. On the other hand, it has been demonstrated that oxytocin is not transferred across the placenta in sheep and humans (Patient et al, 1999;Glatz et al, 1980). In addition, the placenta in pigs is epitheliochorial (it has two complete epithelia and isolates the fetus from the mother) and in humans it is hemochorial (it provides direct access to maternal blood for oxygen-CO 2 exchange and other maternal-fetal transport including glucose and aminoacids) (Enders and Carter, 2004), we therefore consider that our results were related to the actions of oxytocin on the uterine muscle without any direct effects on the piglets.…”
Section: Discussionmentioning
confidence: 99%
“…This efficacy may be supported by our results since the uterus was able to respond to oxytocin at advanced stages of the parturition process. On the other hand, it has been demonstrated that oxytocin is not transferred across the placenta in sheep and humans (Patient et al, 1999;Glatz et al, 1980). In addition, the placenta in pigs is epitheliochorial (it has two complete epithelia and isolates the fetus from the mother) and in humans it is hemochorial (it provides direct access to maternal blood for oxygen-CO 2 exchange and other maternal-fetal transport including glucose and aminoacids) (Enders and Carter, 2004), we therefore consider that our results were related to the actions of oxytocin on the uterine muscle without any direct effects on the piglets.…”
Section: Discussionmentioning
confidence: 99%
“…However, others could not confirm OT passage across the placenta in vivo (Patient et al, 1999). Moreover, in addition to the placenta, OT degrading placental leucine aminopeptidase and the fetal blood-brain barrier may only permit a small fraction of maternal OT to reach the fetal brain.…”
Section: Ot Pathways In the Intergenerational Transmission Of Matementioning
confidence: 99%
“…The reported increase in fetal plasma oxytocin concentration during spontaneous labour (Chard et al 1971) has not been confirmed in studies which controlled for the effect of maternal analgesia (Patient et al 1999). It is thus unlikely that labour is initiated by an increase in fetal oxytocin.…”
Section: Amniotic and Fetal Oxytocin And Vasopressin Concentrationsmentioning
confidence: 85%